2013
DOI: 10.2214/ajr.12.8546
|View full text |Cite
|
Sign up to set email alerts
|

Cam and Pincer Femoroacetabular Impingement: CT Findings of Features Resembling Femoroacetabular Impingement in a Young Population Without Symptoms

Abstract: The CT finding of FAI-like features was made with high frequency in a young symptom-free population. Cutoff values for defining morphologic abnormalities associated with FAI may have been set too low in the current literature. Alpha angle measurements in the radial plane may be a more accurate quantitative assessment of asphericity of the femoral head-neck junction than are measurements in the axial oblique plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
1
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 31 publications
5
59
1
1
Order By: Relevance
“…1A). Anterior femoral head-neck offset was also observed on the oblique-axial plane [11,26], measuring the offset distance between the two tangents of the anterior femoral head and neck (Fig. 1A).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A). Anterior femoral head-neck offset was also observed on the oblique-axial plane [11,26], measuring the offset distance between the two tangents of the anterior femoral head and neck (Fig. 1A).…”
Section: Methodsmentioning
confidence: 99%
“…1E-F) [10,15]. Acetabular version was measured on the transverse plane coincident with the left and right femoral head centers [11,12,41]. This angle was formed by the line connecting the anterior and posterior acetabular notches and the perpendicular axis to the posterior acetabular notch (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In only a few studies have both the cam and pincer type radiological parameters been analyzed in asymptomatic patients. For instance, Chakraverty et al (2) found at least one abnormal parameter in 66% of 100 joints, and two or more abnormal parameters were present in 29% of the joints without symptoms. In another study, Kang et al (13) found that 39% of 100 joints had at least one parameter, and that 11% had more than one parameter associated with FAIs in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Femoroacetabular impingement (FAI) is one cause of hip pain, and is an under-recognized cause of early osteoarthritis, especially in young and active people (1,2). The prevalence of FAI in adults is approximately 10-15% (3) and, depending on the clinical and radiographic findings, two types of impingement (which are often present in combination) can be distinguished: the cam type and the pincer type.…”
Section: Introductionmentioning
confidence: 99%